Empirical performance models of hot in-place recycling of asphalt pavements. Issue 12 (2nd December 2017) - Yu, Bin; Liu, Qiang; Tian, Xin; Zhou, Lan; Lin, Mei
Abstract: Hot in-place recycling (HIR) is deemed as an environmentally competing maintenance strategy to restore asphalt pavement quality. However, there is still lack of quantitative description of the long-term performances of HIR sections and in this study, field data before and after HIR implementation were collected to build empirical models for this purpose. For the rutting model, an adjusting factor was designed to calibrate the rutting development of HIR sections to account for the effect of pavement structure damage before rehabilitation. A two-stage modelling process was used to fix the zero-inflated nature of transverse crack distribution, integrating both the crack initiation and propagation model. Correlation coefficient of error terms for the two models ρ is −0.66 ( p -value = 0.05), demonstrating the importance of the special treatment of 'crack-free' pavement sections. Smoothness and skid resistance properties in terms of international roughness index and side fiction coefficient were best described by linear models within the given periods. Significant factors ( p -value ≤ 0.05) in those models exert different levels of impacts on respective indicators. For instance, while traffic load after HIR implementation dominates rutting development, service year after HIR implementation, base course type and surface layer mix are top three factors influencing both the crack initiation and propagation. The developed model set can be readily used to predict the performances of HIR sections.